A Technique to Realize Aperture Coupled Microstrip Patch as a Truly Low Cross-Polar Antenna by Mitigating the Major Issues Over its Skewed Radiation Planes - Sk Rafidul; Chandrakanta Kumar; Debatosh Guha (IEEE Open Journal of Antennas and Propagation, 2023)
Aperture-fed microstrip patch is typically known for its low cross-polarized (XP) radiations, however it stands true only over its orthogonal plane. The same, over the diagonal planes are as high as that for any other common feeds. This specific issue has been addressed and successfully resolved by proposing a technique for the first time. This introduces a pair of additional printed loops adjacent to the radiating patch. Detailed investigations leading to the design insight have been presented. A C-band rectangular patch promises as much as 7 dB suppression in the diagonal plane XP level keeping the overall performance across the principal radiation planes unchanged. This is an important step in keeping the XP levels for an aperture-fed antenna truly low thus maintaining more than 22 dB of co- to cross-polar isolation over the entire azimuth.